The Exploration of Geometrical Concept in Batik Pamekasan - Septiadi, Dimas Danar; Kohar, Ahmad Wachidul; Sholehein, Akmalus; Zayyadi, Moh.; Basri, Hasan (Universitas Negeri Surabaya, 2023)
Indirectly, mathematical themes can be found throughout Indonesia's unique culture, one of which is mathematics in batik cultural items. Exploring ethnomathematics will be really beneficial. Apart from acquiring the concept of mathematics in Indonesian culture, it can also sharpen Indonesian culture's sense of love for the nation. The purpose of this study is to describe the philosophical meaning of the geometrical concepts contained in Pamekasan batik, the geometrical concepts contained in Pamekasan batik, and the implementation of Batik pamekasan as the context in learning geometry. This is ethnomathematics study which gather the data by observation and interview. The interview held two regions in Pamekasan with four informants. As a result, scholars aim to conduct an ethnomathematics examination of traditional Pamekasan batik. This research shows that aside from the Batik itself, the mathematical objects found in Batik each have their own meaning and hopes. As a result, mathematical motifs such as the point that depicts a rice or maize seed have philosophical significance. Meanwhile, reflection reveals that human life requires balance. Each mathematical object in the pattern has its own meaning. Meanwhile, geometrical objects in Batik Pamekasan are two-dimensional figures such as circles, rectangles, squares, lines, points, angles, and curves. In addition, transformative geometry like as rotation, reflection, and translation exist in Batik Pamekasan. Besides, batik pamekasan can be used as the context in learning geometry. This can be seen from the learning outcomes that was written in Merdeka curriculum. Moreover, problem-based learning and project-based learning are two models that support ethnomathematics-based learning.